TERAPI MUSIK UNTUK MENGURANGI TINGKAT STRES AKADEMIK PADA SISWA SMA NEGERI 5 BANDA ACEH - Dedi Prasetyo; Abu Bakar; Nurbaity Bustamam (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
This study entitled "music therapy to reduce Academic stress levels In Public High School 5 Banda Aceh". As for the purpose of writing is to know the academic stress levels decrease in students of Public High School 5 Banda Aceh through music therapy-type Islamic instruments. This paper is a research experiment by using pre-experiment design one group pretest-posttest and is a quantitative approach. The research was carried out in Public High School 5 Banda Aceh. The sampling technique was purposive sampling, while the subject is students who have high academic stress levels, five students obtained to have such criteria. Data collection method using the 0-4 scale. Data analysis using a non-parametric statistical test which was Wilcoxon Signed Rank. The results show that the average academic stress score is of five people before treatment were 63, while after music therapy treatment the average score of academic stress decreased to 34.6. The Z statistic obtained from Wilcoxon Signed Rank Test was -2.023 with a significant level of 0.043 which is smaller than 0.05. The results indicated that music therapy can be used to decrease the level of academic stress.